Estimation of Maximum Tensile Stress on Rigid Pavement for Varying Surface Temperature - Das, Deepa; Pal, Dibyendu (Journal of Engineering and Sustainable Development, 2025)
The load transfer ability of rigid pavement degrades over time due to repeated vehicular loads and environmental factors, such as temperature. The temperature disparity between a slab’s upper and lower layers has more impact on the development of stresses on a rigid pavement. Failing of it occurs when the developed stresses exceed the critical stress. This work examines fluctuating surface temperatures’ impact on the maximum tensile stress within a single slab system. The pavement was modeled and analyzed using the finite element software EverFE2.26. It was observed that varying surface temperature affects the maximum tensile stress. A regression model was developed to estimate the maximum tensile stress for any surface temperature (0°C-50°C), temperature differential, and other slab and axle parameters. The R2 value of the regression model was obtained as 0.888. The regression model was validated with another set of maximum tensile stress data obtained from EverFE2.26. The model resulted in less than 10% difference. This model allows for directly estimating the maximum tensile stress in the rigid pavement, accommodating parameter changes. However, further model refinement may be carried out for multiple slabs.